2022
DOI: 10.1371/journal.pone.0264007
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of anemia and associated factors among adult diabetic patients attending Bale zone hospitals, South-East Ethiopia

Abstract: Background Anemia found in diabetes patients is often unrecognized like many other chronic diseases. The occurrence of anemia is also an additional burden to the micro vascular complications of patients with diabetes. In the selected study structure no published data were found on the prevalence of anemia and associated factors in diabetic patients. Hence, the findings of this study are very fruitful as an input for further studies and after the repetition of similar studies in different frameworks. It is help… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 15 publications
0
8
2
1
Order By: Relevance
“…24 Also, Hisham and colleagues in Saudi Arabia reported a much lower prevalence (22%) of anemia in T2DM patients compared to our study. 25 According to the findings of the Solomon et al 26 the prevalence of anemia among adult diabetes mellitus patients was 18.1%, which is much lower compared to our study. Disparities in the previous and current findings in anemia prevalence could be due to T2DM patients.…”
Section: Discussioncontrasting
confidence: 54%
“…24 Also, Hisham and colleagues in Saudi Arabia reported a much lower prevalence (22%) of anemia in T2DM patients compared to our study. 25 According to the findings of the Solomon et al 26 the prevalence of anemia among adult diabetes mellitus patients was 18.1%, which is much lower compared to our study. Disparities in the previous and current findings in anemia prevalence could be due to T2DM patients.…”
Section: Discussioncontrasting
confidence: 54%
“…followed by Diabetes, Metabolic Syndrome and Obesity 2023:16 https://doi.Abbreviations: CS, cross-sectional; NR, not reported. https://doi.org/10.2147/DMSO.S421851 DovePress Diabetes, Metabolic Syndrome and Obesity 2023:16eight (33.33%) studies from Africa,27,[33][34][35][36]40,49,50 one (4.17%) study from Europe, 42 one (4.17%) study from Australia,…”
mentioning
confidence: 99%
“…(15) Solomon et al reported that the frequency of anemia in both genders was almost the same, i.e., 19.01% and 21.1% in males and females, respectively. (19) Past studies reported occurrence of anemia in males upto 17%-69% and in diabetic females, 11-30%. (20,21) Females, on the other hand, were more likely to suffer from anaemia than males, according to our findings.…”
Section: Discussionmentioning
confidence: 97%
“…(18) Solomon et al resulted that among anemic patients, 81.4% had the normocytic hypochromic type of anemia. (19) According to prior research, longterm poorly controlled diabetes in patients without abnormal RFTs was linked to normocytic normochromic anemia. (23) The differences in the above results may be attributed to different populations included in the studies.…”
Section: Discussionmentioning
confidence: 99%